Emergency mental health presentations in children with autism spectrum disorder and attention deficit hyperactivity disorder. (8th May 2021) - Bourke, Elyssia M; Say, Daniela F; Carison, Anna; Hill, Ashley; Craig, Simon; Hiscock, Harriet; Babl, Franz E; O'Donnell, Sinead M
Abstract : Aim: To characterise the key features and management of young people presenting to the emergency department (ED) with a mental health (MH) complaint and a known diagnosis of autism spectrum disorder (ASD) or attention deficit hyperactivity disorder (ADHD). Methods: Retrospective review of all ED MH presentations in children aged 7–17 years, presenting over a 12‐month period from the 1st of January 2018 to the 31st of December 2018, to the Royal Children's Hospital in Melbourne, Australia. Univariate analyses were carried out to examine the relationship between an underlying diagnosis of ASD and/or ADHD and a number of key presentation variables. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated for ED management outcomes. Results: There were 374 presentations in this cohort, representing 28% of the total MH presentations in 2018. The most common reason for presentation was acute severe behavioural disturbance. Young people with ASD and ADHD were at increased risk of having an acute crisis team response activated (ASD RR 2.3, CI 1.6–3.3, ADHD RR 2.2, CI 1.2–4.1). Compared to those without either diagnosis, young people with ASD were more likely to be physically restrained (RR 2.8, CI 1.7–4.6), managed in seclusion (RR 3.3, CI 1.7–6.4) and to receive medication to assist with behavioural de‐escalation (RR 2.8, CI 1.6–4.9). Conclusions: Children with ASD and/or ADHD represent one‐quarter of all children presenting to the ED with MH complaints. They experience high rates of acute severe behavioural disturbance. Future research is needed to co‐design, implement and evaluate better approaches for their management.